Introduction to social research : Quantitative and qualitative approaches - Punch, Keith F. (London : Singapore : New Delhi : SAGE Publications Ltd, 2009)
Introduction to Social Research presents the essential elements of both qualitative and quantitative approaches for conducting empirical research in the social sciences.
Includes references and index.
Keywords: Social science -- Research